Comparative Study of Two Dimensional Boundary Layer over NACA 23012 and NACA 23021 Airfoils by Using Keller’s Box Method - K Sivak Kumar, Vinod Kumar; Abdullah, Aslam; Basuno, Bambang (Journal of Advanced Mechanical Engineering Applications, 2022)
This paper begins with general description on various methods for solving boundary layer equation. In particular, Prandtl's boundary layer equation is a simplified version of Navier-Stokes equation that is solved integrally. Analysis order of magnitude can be used to solve laminar and turbulent flow problems along the boundary layer. A more complex technique based on Keller’s box method is also discussed. This study aims at utilising a developed computer code which allows one to predict the development of boundary layer characteristics along airfoils’ surface. Two airfoils which are NACA 23012 and NACA 23021 were taken into account. The ability of Keller’s box method to solve the boundary layer equation prevails through correct skin friction, momentum thickness, and shape factor distributions over the surfaces.